Transformasi Konstitusi Indonesia: Dari Kemerdekaan Hingga Era Reformasi - Yunita Suarda, Rahma; Hadijah Wahid, St.; Risnawati; Yuliana; Ningra HS, Wirga; Siska (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
The history of Indonesia's constitution has gone through various stages of development. Each stage introduced a distinctive model of state governance. However, due to past traumas, particularly from the New Order's misuse of the constitution to support its centralistic and authoritarian power, the idea of amending the 1945 Constitution (UUD 1945) emerged.The development of Indonesia's constitution can be categorized into several periods. The first period was the implementation of the 1945 Constitution, followed by the second period under the 1949 Constitution of the Republic of the United States of Indonesia (Konstitusi RIS 1949). The third period saw the enactment of the 1950 Provisional Constitution (UUDS 1950), and the fourth period marked the reinstatement of the 1945 Constitution along with its explanatory notes. Subsequently, the 1945 Constitution was amended successively in 1999, 2000, 2001, and 2002, using the version effective from July 5, 1959, as the standard for revisions outside the main text, which later became an inseparable appendix to the 1945 Constitution. Amending the constitution is undoubtedly not a simple task. The constitution serves as the primary design of the state, regulating fundamental and strategic matters, including the structure of power, the relationships among state organs, and human rights. The process of amending the 1945 Constitution was carried out in four stages. These amendments faced criticism for various shortcomings, prompting the idea of forming a Constitutional Commission to address these issues and assist with future amendments. Almost all countries undergoing transitions to democracy consider constitutional reform an integral part of their political renewal. Constitutional reform is seen as so crucial that its presence is deemed necessary. It is not always clear when a country in transition begins its constitutional reform. According to various literature on democratic transitions, the experiences of countries in this regard vary widely. For instance, the Philippines initiated constitutional reform by establishing a constitutional commission tasked with drafting a new constitution shortly after President Marcos was overthrown and the new administration under Cory Aquino was established This article aims to explore the development of Indonesia's constitution from the early days of independence to the constitutional reforms following the New Order era, as well as an analysis of the results of the amendments to the 1945